Penegakkan Hukum dalam Upaya Pencegahan dan Rehabilitasi Bagi Korban Penyalahgunaan Narkotika, Psikotropika, dan Zat Adiktif Lainnya (Napza) dalam Rangka Memperkuat Ketahanan Nasional - Irman Putra (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The high threat posed by narcotics and the dynamic strategic environment for narcotics means that Law Number 35 of 2009 concerning Narcotics is considered to be no longer compatible and therefore needs to be revised. The purpose of this research is to show that the initial picture leads us to awareness of the condition of "Indonesia's Drug Emergency" which is still occurring today. Qualitative research uses descriptive methodology to collect data methodically, factually and wisely according to the description at the time of the research. The results of this research show that several efforts to optimize coordination and collaboration between related institutions are needed in preventing the distribution of narcotics and rehabilitation of victims of drug abuse.